General and specific combinatory adequacy of regular and high-quality protein maices - Manjarrez Salgado, Margarito; Palemón Alberto, Francisco; Gómez Montiel, Noel Orlando; Espinosa Calderón, Alejandro; Rodríguez Herrera, Sergio A.; Damián Nava, Agustín; Hernández Castro, Elías; Cruz Lagunas, Blas (Revista Mexicana de Ciencias Agrícolas, 2018)
Agronomic traits and genetic components are indicators of quality; additional factors are important to study the traits of germplasm in a breeding program. The effects of general (GCA) and specific (SCA) combining adequacy and the type of gene action for agronomic traits of regular maize (Zea mays L.) seeds and high-quality protein were analysed. The genetic material consisted of 10 maize inbred lines: four of regular grain and six high-quality protein. The variables analysed were: days to male and female flowering, plant and ear height, plant and ear score, and grain yield. The results showed significant variation among genotypes (p≤ 0.01) on the effects of GCA and SCA for all agronomic variables. Lines were identified as: T-44, B-41, LT-155, T-45 and CML-144 C, with higher values   of GCA, being 0.6379, 0.4592, 0.3286, 0.2945 and 0.3382 t ha-1, respectively, for grain yield. Furthermore, outstanding materials based on its identified SCA crosses 4 * 8 (B-41 * CML-144), 1 * 5 (T-45 * CLQ-6203), and 2 * 7 (T-44 * CML- 142), with SCA estimated values for grain yield of 1.0875, 0.9544 and 0.7591 t ha-1, respectively. The type of additive gene action was the predominant in agronomic characters.
Keywords: Zea mays L.; agronomic traits; general and specific combining adequacy; regular grain and high-quality protein